2003
DOI: 10.1034/j.1600-0854.2004.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid increases the length and volume density of ducts in the rat embryonic pancreas

Abstract: In this study, the role of all-trans retinoic acid (RA) on the proliferation of rat embryonic pancreas ducts and on the proportion of insulin cells was investigated. All-trans RA (10-6 m) was added to Ham's F12.ITS serum-free medium in which 12.5 day rat dorsal pancreatic buds were cultured on Matrigel. Control explants were cultured on Matrigel in Ham's F12.ITS alone or in Ham's F12.ITS containing ethanol (the diluent for RA). After a 7 day culture period, explants were incubated with bromodeoxyuridine (BrdU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The ductal epithelial cells regress into a least differentiated state and acquire characteristics of progenitor cells, since external signals were able to direct their differentiation to an endocrine, acinar or mature duct phenotype (Bounwens and De Blay, , Kritzik et al, , Song et al, ). RA has been reported to enhance proliferation and survival of cells (Erasmus et al, , Lin and Wu, , Noy, ). In line with our findings, Erasmus et al () reported that atRA increased the branching of ductal cells during which some cells broke away from the duct epithelium and lost their attachment to the basement membrane to form islets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ductal epithelial cells regress into a least differentiated state and acquire characteristics of progenitor cells, since external signals were able to direct their differentiation to an endocrine, acinar or mature duct phenotype (Bounwens and De Blay, , Kritzik et al, , Song et al, ). RA has been reported to enhance proliferation and survival of cells (Erasmus et al, , Lin and Wu, , Noy, ). In line with our findings, Erasmus et al () reported that atRA increased the branching of ductal cells during which some cells broke away from the duct epithelium and lost their attachment to the basement membrane to form islets.…”
Section: Discussionmentioning
confidence: 99%
“…RA has been reported to enhance proliferation and survival of cells (Erasmus et al, , Lin and Wu, , Noy, ). In line with our findings, Erasmus et al () reported that atRA increased the branching of ductal cells during which some cells broke away from the duct epithelium and lost their attachment to the basement membrane to form islets. Also, Penny and Kramer () found that atRA in vitro caused a significant increase in the proportion of insulin‐secreting cells in the pancreas of the chick accompanied with an increase in duct profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatic ductal cells isolated from pre‐diabetic non‐obese diabetic (NOD) mice can be induced to form functional islets, which are able to reverse diabetes when transplanted into the diabetic counterparts of these donor mice 44, 45. Furthermore, more recent in vitro work performed on ductal cells from the rat suggests that clusterin may induce the differentiation of β‐cells 46, and another study has suggested that all‐trans retinoic acid can act to induce the differentiation of β‐cells from rat ductal cells 47.…”
Section: Intra‐pancreatic Stem Cellsmentioning
confidence: 99%
“…However, administration after neurulation did not affect development of Langerhans islets. Retinoic acid increased insulin secreting cells by stimulating production of extra progenitor cells (Erasmus et al 2003). Exogenous retinoic acid can increase insulin secretion both the fetal and adult islets.…”
Section: Discussionmentioning
confidence: 99%